2014
DOI: 10.1603/ec13511
|View full text |Cite
|
Sign up to set email alerts
|

An EPG Study of the Probing Behavior of Adult <I>Bemisia tabaci</I> Biotype Q (Hemiptera: Aleyrodidae) Following Exposure to Cyantraniliprole

Abstract: Cyantraniliprole is a novel insecticide for control of multiple chewing and sucking insect pest species including the sweetpotato whitefly Bemisia tabaci (Gennadius), which is one of the most important polyphagous pests in tropical, subtropical, and Mediterranean regions. This study aims to evaluate the effects of cyantraniliprole on the probing behavior of B. tabaci on tomato. Electrical penetration graph data indicated that on plants treated with cyantraniliprole (foliar application), adult whiteflies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 75 publications
(77 reference statements)
0
32
0
1
Order By: Relevance
“…The early reduction in feeding produced by cyantraniliprole could potentially decrease the risk of virus transmission in the early stages of plant growth. A recent study with the use of the electrical penetration graph (EPG) demonstrated that B. tabaci biotype Q adults feeding on plants treated with cyantraniliprole (foliar application) were not able to reach the phloem and consequently did not perform phloem salivation (during which inoculation of geminiviruses occurred) and phloem sap ingestion (during which geminiviruses were acquired by the whiteflies) [40]. The authors concluded that the complete failure of B. tabaci adults to feed from the phloem of tomato plants treated with cyantraniliprole could be due to the rapid feeding cessation produced by the mode of action of this insecticide.…”
Section: Discussionmentioning
confidence: 99%
“…The early reduction in feeding produced by cyantraniliprole could potentially decrease the risk of virus transmission in the early stages of plant growth. A recent study with the use of the electrical penetration graph (EPG) demonstrated that B. tabaci biotype Q adults feeding on plants treated with cyantraniliprole (foliar application) were not able to reach the phloem and consequently did not perform phloem salivation (during which inoculation of geminiviruses occurred) and phloem sap ingestion (during which geminiviruses were acquired by the whiteflies) [40]. The authors concluded that the complete failure of B. tabaci adults to feed from the phloem of tomato plants treated with cyantraniliprole could be due to the rapid feeding cessation produced by the mode of action of this insecticide.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been widely used to investigate the characteristics of host plant resistance to sucking insect pests and to interpret the mechanisms of plant pathogen transmission by insect vectors . Moreover, the EPG has been applied to study the mode of action of insecticides …”
Section: Introductionmentioning
confidence: 99%
“…Although laboratory and field experiments provide useful information on mortality caused by the application of an insecticide, comprehensive information on how an insecticide affects the feeding behaviour of insects requires other methods . Among those methods, electropenetrography (EPG) is the most rigorous method for examining the effects of an insecticide on the feeding behaviour of piercing‐sucking insect pests and on the damage to plant tissues . In EPG, an insect and feeding substrate are incorporated into an electrical circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have been conducted to evaluate the effects of insecticides on the feeding behaviour of sap‐sucking insects, but the effect of flonicamid on the feeding behaviour of A. biguttula has not yet been examined. This study characterised the effects of flonicamid on the feeding behaviour of A. biguttula on cotton plants treated with the systemic insecticide.…”
Section: Introductionmentioning
confidence: 99%